EDUCATION DIRECTED TO STUDENTS IN TEACHING THE SCIENCE OF EDUCATION IN PRIMARY GRADES DISTINCTIVE ASPECTS (Academia Science Repository, 2023)
In this article, student-oriented education and solving the problems that arise in this process, student-oriented education system and the essence of education in primary grades development, intellectual and practical skills, formation of the system of qualifications is intended to increase the results of the work carried out in this regard.